f(x) = x^2 + 4 h(x) = 2x - 1/ x + 3 Find (f o h)(x) (f o h)(x) = f(h(x)) f(2x-1 / x +3) = (2x-1 / x +3)^2 + 4 f(2x-1 / x +3) = (4x^2 - 4x + 1 / x^2 + 6x +9 ) + 4 Did I do this correctly?

Follow Math Help Forum on Facebook and Google+

Hello, Originally Posted by moonman f(x) = x^2 + 4 h(x) = 2x - 1/ x + 3 Find (f o h)(x) (f o h)(x) = f(h(x)) f(2x-1 / x +3) = (2x-1 / x +3)^2 + 4 f(2x-1 / x +3) = (4x^2 - 4x + 1 / x^2 + 6x +9 ) + 4 Did I do this correctly? Yes But you can also put 4 in the fraction : and then expand

Originally Posted by Moo Hello, Yes But you can also put 4 in the fraction : and then expand ahh! Thank you

View Tag Cloud